1999
DOI: 10.1037/0278-7393.25.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing and initial phoneme criterion in naming words: Evidence from frequency effects on onset and rime duration.

Abstract: This study reports 4 experiments that investigated the locus of temporal effects of printed word frequency in speeded-naming tasks. Response latencies and onset durations are shorter for high-frequency words compared with low-frequency words, but there is no effect of frequency on rime durations. These results can only be accounted for if (a) phonemes are activated in parallel and not sequentially from left to right and (b) the criterion to initiate pronunciation is based on the initial phoneme and not the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 52 publications
5
44
1
Order By: Relevance
“…In single word production, a longer duration of the initial phoneme has been reported for words entailing irregular vowel pronunciation, compared to words with a regular vowel pronunciation (Kawamoto, Kello, Jones, & Bame, 1998). Also, lexical frequency seems to affect initial phoneme durations, but not rhyme durations (Kawamoto, Kello, Higareda, & Vu, 1999; see also Mousikou & Rastle, 2015). Lexical frequency effects have actually been detected in a reading aloud task with delayed responses (Balota & Chumbley, 1985), but this result has been debated (Monsell, Doyle, Haggard, 1989;Balota & Chumbley, 1990).…”
Section: Introductionmentioning
confidence: 88%
“…In single word production, a longer duration of the initial phoneme has been reported for words entailing irregular vowel pronunciation, compared to words with a regular vowel pronunciation (Kawamoto, Kello, Jones, & Bame, 1998). Also, lexical frequency seems to affect initial phoneme durations, but not rhyme durations (Kawamoto, Kello, Higareda, & Vu, 1999; see also Mousikou & Rastle, 2015). Lexical frequency effects have actually been detected in a reading aloud task with delayed responses (Balota & Chumbley, 1985), but this result has been debated (Monsell, Doyle, Haggard, 1989;Balota & Chumbley, 1990).…”
Section: Introductionmentioning
confidence: 88%
“…If we assume, based on the frequency-of-use hypothesis, that the frequency values of the words for bilinguals are lower than for monolinguals, we should expect shorter durations for the latter group. 1 Second, some studies have revealed that the ease with which word retrieval is achieved may have an impact not only on the speed with which utterances are initiated (onset latencies) but also on the corresponding articulatory durations (Balota et al 1989;Kawamoto et al 1998Kawamoto et al , 1999Kello et al 2000;Kello 2004 although see Damian, 2003). Hence, given that word retrieval appears to be more costly for bilinguals in comparison to monolinguals, we may expect to find a trace of such difficulty in articulatory durations.…”
Section: Introductionmentioning
confidence: 98%
“…made a connection between response durations and rate of processing on the basis of cascaded articulation. Cascaded articulation is the hypothesis that, under some circumstances, response processing and response execution can overlap in time (also see Kawamoto, Kello, Jones, & Bame, 1998;Kawamoto, Kello, Higareda, & Vu, 1999). If articulation was cascaded in the tempo-naming study, then one would expect a change in the rate of response processing to be reflected in a change in the rate of response execution.…”
Section: The Rate Of Processing Hypothesismentioning
confidence: 99%